Tinkering with a tanker—slow evolution of a Swedish ecosystem approach. (2nd February 2017) - Österblom, Henrik; Hentati-Sundberg, Jonas; Nevonen, Nea; Veem, Katarina
Abstract : The ecosystem approach is a salient policy paradigm originating from a scientific understanding of the reality of complex ecosystem dynamics. In this article, we investigate how Swedish national marine policies and practice between 2002 and 2015 have changed towards an ecosystem approach. Government documents, the scientific literature, institutional changes, changes in legislation, pilot projects, and changes in science and public opinion were reviewed and combined with information from expert interviews. We found that changes in policy and practice have slowly stimulated the development of an ecosystem approach, but that limited political leadership, challenges of coordination, different agency cultures, and limited learning appears to be key barriers for further and more substantial change. We compare and contrast the Swedish national process of change with other documented experiences of implementing an ecosystem approach and find that several countries struggle with similar challenges. Substantial work still remains in Sweden and we provide suggestions for how to stimulate further and more substantial change at the national level.